“I Think It’s Too Early to Know”: Gender Identity Labels and Gender Expression of Young Children With Nonbinary or Binary Transgender Parents - Riskind, Rachel G.; Tornello, Samantha L. (Frontiers in Psychology, 2022)
Little is known about gender expression among children with transgender parents. In the United States, we surveyed 64 nonbinary or binary transgender parents of children aged 18 to 71 months. Most parents reported a marginalized sexual identity and a White racial identity. Many declined to label their child’s gender identity, and this was particularly true among those with younger children. Scores indicated that, on average, children’s play was conventionally gendered. However, scores indicated significantly more gender-expansive play in the present sample than in normed samples, particularly among children assigned male at birth. Findings support transfamily theory (McGuire et al., 2016) and illustrate differences among families with nonbinary and binary transgender parents.